Smartphones as multipurpose intelligent objects for AAL: two case studies - Spinsante, Susanna; Montanini, Laura; Gambi, Ennio; Lambrinos, Lambros; Pereira, Fábio; Pombo, Nuno; Garcia, Nuno (My University, 2017)
The increasing adoption of smartphones among older adults, especially in most developed countries, suggests they can be used not only for personal communications, but also in the framework of Active and Assisted Living solutions. This paper addresses two case studies in which a smartphone, when equipped with a proper software application, may operate as an inactivity monitor, and a drug management assistant, respectively. Activity monitoring is carried out by targeting the user’s interaction with the smartphone related to incoming, outgoing, and lost calls. In the latter case, an application processes images of drugs boxes captured by the smartphone camera, to automatically recognize the name of the drug, and inform the user about the corresponding prescription. Experimental results show this kind of approach is technically feasible and may provide satisfactory performance through a very easy interaction, thus supporting improved medication adherence by patients.
Keywords: Activity monitoring; Ambient assisted living; Drug management; Mobile device